Same-Day Versus Next-Day Repair of Fovea-Threatening Primary Rhegmatogenous Retinal Detachments. (3rd May 2016) - Gorovoy, Ian R.; Porco, Travis C.; Bhisitkul, Robert B.; de Juan, Eugene; Schwartz, Daniel M.; Stewart, Jay M.
Abstract: Purpose : To evaluate the outcomes of same-day versus next-day repair of fovea-threatening rhegmatogenous retinal detachments (FT RRD). Design : Retrospective, multi-surgeon observational case series. Methods : Operative reports and medical records were reviewed to evaluate a number of visual and anatomic outcomes, including presenting features, intraoperative complications, and postoperative results in the repair of primary FT RRD undergoing same-day versus next-day repair with scleral buckling, pars plana vitrectomy, or both procedures. Participants : A total of 96 consecutive patients (43 same-day, 45 next-day, and eight two days later) were compared. Results : There was no statistically significant difference in visual outcomes between same-day and next-day repair at postoperative months 3 and 6 and at last follow-up (month 3 mean BCVA 20/30 same day; 20/32 next day; p  = 0.82). Preoperative vision was strongly correlated with postoperative acuity. Effect of differences in length or type of visual symptoms, location of RRD, gender, or lens status on postoperative month 3 best-corrected visual acuity (BCVA) was not statistically significant. Overall, 85% of patients had a BCVA of 20/40 or better at postoperative month 3. Reoperation rate and intraoperative complications were not statistically different between the two groups. Re-attachment was achieved in all but one patient in both groups. Time in the operating room was longer for same-day surgery (2.98 ± 0.46 hours) compared to next-day surgery (2.54 ± 0.38 hours) ( p  < 0.001), which was statistically significant even when factoring in the type of surgery performed. However, one case did progress to a macula-off detachment in a superior RRD with breaks found in lattice degeneration. Conclusion : Next-day surgery provided equivalent visual outcomes. Emergent, same-day surgery has logistical and resource implications as it may be more expensive, may necessitate rescheduling of previously booked cases, and may limit preoperative examination by the surgeon and perioperative team.